Imaging Findings of Gastric Diverticula - Dominik Schramm; Andreas Gunter Bach; Alexander Zipprich; Alexey Surov (The Scientific World Journal)
Introduction. Gastric diverticula (GD) are very rare. Computer tomographic findings in GD have been reported only as case reports previously. The aim of this study was to estimate the prevalence of GD on computed tomography (CT) and to analyze their radiological appearances. Materials and Methods. From 2006 to 2013, a total of 14,428 patients were examined by abdominal/thoracic CT at our institution. GD were diagnosed in 18 (0.12%) patients (13 women and 5 men, median age, 64 years). In 9 patients, additional endoscopy and in 7 patients upper gastrointestinal investigation with contrast medium were performed. Magnetic resonance imaging (MRI) was available for 3 cases. Results. In all patients GD were diagnosed incidentally during CT examination. The diverticula were located at the posterior wall of the gastric fundus below the esophagogastric junction. On CT, GD presented as cystic lesions with a thin wall and an air fluid level, located behind the stomach between spleen, adrenal gland, and crus of the left diaphragm. Conclusion. The prevalence of GD encountered in our CT series is 0.12%. GD demonstrate typical CT appearances, namely, cystic lesions located in the left paravertebral region. The radiologist should be familiar with this finding to avoid possible misinterpretations.